Membrane Condenser as efficient pre-treatment unit for the abatement of particulate contained in waste gaseous streams. Issue 5 (October 2020) - Brunetti, Adele; Macedonio, Francesca; Cui, Zhaoliang; Drioli, Enrico
Graphical abstract: Highlights: Membrane condenser aids in the abatement of particulate of waste gaseous streams. Validation of simulations with experimental results Retention efficiency strongly depends on permeating stream velocity and membrane pore diameter Retention efficiency not influenced by particle density and condenser temperature An efficient abatement of particles requires a membrane with narrow pore distribution. Abstract: The removal of particulate matter from the gaseous streams emitted from industrial plants has become one of the most relevant environmental issues because of its hazardous effects on human health. In this work, we propose the use of membrane condenser as a pre-treatment unit for the retention of particles contained in waste gaseous streams. We calculated the retention efficiency of membrane condenser on the basis of the aerosol technology and we analysed the various contributions related to interception, impaction, diffusion, and gravitation. The variation of the retention efficiency was analysed considering a particle diameter ranging from 0.1 to 10 μm, at various density of the particle itself. In addition, the effect of the membrane properties such as thickness, pore diameter, permeating flux velocity as well as of the temperature of the gaseous stream to be treated was investigated. The gas velocity resulted a determining variable in the retention efficiency, specifically for particles with a diameter lower than 1 μm, showing 10–50% variation for a particle diameter of 0.3 μm. The same drop was observed when the membrane pore diameter passed from 0.2 to 3 μm, confirming the significant importance of having membranes with a narrow pore distribution.